LAVENDER MARRIAGE SEBAGAI KEKERASAN SEKSUAL PSIKIS DALAM HUKUM INDONESIA: REINTERPRETASI PASAL 4 UU TPKS MELALUI PERSPEKTIF HUKUM PROGRESIF - Mufatihatuttaubah Rorom Ika Putri; Umi Sumbulah; Ahmad Izzuddin (LPPM STAI Muhammadiyah Probolinggo, 2026)
The practice of lavender marriage, which is motivated by one party's dishonesty regarding their sexual orientation, has significant psychological and social consequences for the couple. However, to date, there are no regulations that explicitly govern and provide legal protection against this practice, so it has not been dealt with optimally. This article aims to review legal regulations related to psychological sexual violence in order to formulate a direction for legal reform that can respond to the practice of lavender marriage. This study uses a normative-qualitative method with a document study approach to interpret Article 4 paragraph (2) letter d of the Sexual Violence Criminal Law (TPKS Law) through a progressive legal perspective. The results of the study show that this article can be interpreted more broadly as a form of psychological sexual violence that includes the practice of lavender marriage and various other forms of non-conventional sexual violence. Thus, the application of progressive law encourages the law not to stop at normative texts, but to function adaptively and humanistically in responding to the needs of substantive justice and realising justice and community welfare